CONTRIBUTION OF BALKONDES "SAKA PITU" AS A SUPPORTER OF BOROBUDUR KSPN IN INCREASING ECONOMY OF TEGALARUM - Cholisna, Siti Li; Setyaningrum, Dewi; Kumala, Faizah; Yuliani, Nur Laila (Jurnal Analisis Bisnis Ekonomi, 2019)
This research is motivated by the existence of the establishment of the Village Economic Center (BALKONDES) which was initiated by the Ministry of SOEs in 2016 to overcome economic development in Borobudur District. The "Saka Pitu" Balkondes located in Tegalarum Village is the 18th Balkondes out of a total of 19 Balkondes. Balkondes "Saka Pitu" as a supporter of the Borobudur National Tourism Strategic Area (KSPN) and to support the campaign to support Balkondes "Saka Pitu" to promote the Tegalarum community. The sample of this study was 20 informants from Tegalarum residents who were taken based on the Convenience Sampling method. The results of the study announced the contribution of Balkondes "Saka Pitu" as a supporter of the Borobudur National Tourism Strategic Area (KSPN), starting Tegalarum Village to become a tourism village and opening up employment opportunities for the surrounding community. While the influence of Balkondes "Saka Pitu" on improving Tegalarum community in general has not yet had an optimal effect.